Implementasi Heuristik dalam Penelitian Sejarah Bagi Mahasiswa - Ravico Ravico; Endang Rochmiatun; Ira Miyarni Sustianingsih; Berlian Susetyo; Nuzulur Ramadhona (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
The background of this research is that it is still weak and even feels very difficult for history students in writing their final project or thesis. This is due to a lack of understanding of historical research methods. Starting from heuristics to historiography. In order for an understanding of this research method to be carried out properly, it is necessary to have complete understanding of heuristics as a first step. This study uses qualitative research with the steps of observation, researchers see directly the problem and study the literature to examine relevant theories in research. The results of this study obtained that the strategy in the search is bibliographic search, oral source search, artifact search and online source search. Furthermore, the final step is regarding the management of the data sources obtained so that they are arranged periodically.